Cheese : chemistry, physics & microbiology - McSweeney, Paul L. H.; Fox, Patrick F.; Cotter, Paul; Everett, David W. (Elsevier Science, 2017)
Cheese: Chemistry, Physics and Microbiology, Fourth Edition, provides a comprehensive overview of the chemical, biochemical, microbiological, and physico-chemical aspects of cheese, taking the reader from rennet and acid coagulation of milk, to the role of cheese and related foods in addressing public health issues. The work addresses the science from the basic definition of cheese, to the diverse factors that affect the quality of cheese. Understanding these fermented milk-based food products is vital to a global audience, with the market for cheese continuing to increase even as new nutritional options are explored. Additional focus is provided on the specific aspects of the ten major variety cheese families as defined by the characteristic features of their ripening. The book provides over 1000 varieties of this globally popular food. Features new chapters on Milk for Cheesemaking, Acceleration and Modification of Cheese Ripening, Cheesemaking Technology, Low-Fat and Low Sodium Cheesemaking, and Legislation Offers practical explanations and solutions to challenges Content presented is ideal for those learning and practicing the art of cheesemaking at all levels of research and production.